2021
DOI: 10.3390/jcm10214989
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Patients with Ischemic versus Non-Ischemic Cardiomyopathy after Angiotensin-Neprilysin Inhibition Therapy

Abstract: Background: The angiotensin receptor-neprilysin inhibitor (ARNI) decreases cardiovascular mortality in patients with chronic heart failure with a reduced ejection fraction (HFrEF). Data regarding the impact of ARNI on the outcome in HFrEF patients according to heart failure etiology are limited. Methods and results: One hundred twenty-one consecutive patients with HFrEF from the years 2016 to 2017 were included at the Medical Centre Mannheim Heidelberg University and treated with ARNI according to the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Third, we found significant heterogeneity among studies on some outcomes, which might result from the large differences in respect to control drugs, average dose, number of patients at different dose levels, and NYHA functional class among studies. Finally, although some studies reported that different population characteristics could have impacts on the treatment outcome with sacubitril/valsartan, such as the age and etiology differences, we did not conduct subgroup analysis ( 39 , 40 ). Because there was lack of data concerning sacubitril/valsartan therapy with respect to different ages, etiologies of HF, NYHA functional classes, control drugs, duration of follow-up, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we found significant heterogeneity among studies on some outcomes, which might result from the large differences in respect to control drugs, average dose, number of patients at different dose levels, and NYHA functional class among studies. Finally, although some studies reported that different population characteristics could have impacts on the treatment outcome with sacubitril/valsartan, such as the age and etiology differences, we did not conduct subgroup analysis ( 39 , 40 ). Because there was lack of data concerning sacubitril/valsartan therapy with respect to different ages, etiologies of HF, NYHA functional classes, control drugs, duration of follow-up, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Third, cardiac arrhythmias were not described in terms of sustained or non-sustained, fast or slow. Forth, data have shown a possible different effects of sacubitril/valsartan according to the HF etiology and age ( 42 , 43 ). Due to lack of data, the effects of sacubitril/valsartan on the risk of cardiac arrhythmias and SCD according to HF etiology and age remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Any molecular mechanisms, where SV promotes arrhythmia, were not found in the current study. Clinical reports have indicated that SV can increase the incidence of ventricular arrhythmias in patients with HF ( 8 , 14 ), but with short follow-up times and small sample sizes. Etiology, gender differences, and inclusion of high-risk patients may also affect the results ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs that inhibit myocardial remodeling ( 12 ), such as ARNI, may play antiarrhythmic roles by reducing the formation of ectopic impulses and reentry from the upstream mechanism ( 13 ). However, the controversy around SV remains: it increases the incidence of ventricular arrhythmias, especially in patients with ischemic heart disease ( 14 , 15 ), although after adjusting the outcomes, the cardiovascular death caused by etiologies of HF such as ischemic, non-ischemic, and hypertensive cardiomyopathies are similar ( 16 , 17 ). But, in men with ejection fraction of <35%, patients who recently took SV may be more prone to ventricular arrhythmias ( 18 ).…”
Section: Introductionmentioning
confidence: 99%